SISTEM NAMA DIRI MASYARAKAT ETNIS MINANGKABAU: KAJIAN NAMA PANGGILAN PADA MASYARAKAT RANTAU PASISIA DI PARIAMAN - Pramita, Dice Dian; Ermanto, Ermanto; Juita, Novia (Universitas Negeri Padang, 2017)
This article aims to: (1) Describe the pattern of a nickname based on the form used lingual Minangkabau ethnic communities shoreline Pariaman; (2) Describe the category nickname used by its reference Minangkabau ethnic communities shoreline Pariaman; (3) Describe the category nickname based on the sense used Minangkabau ethnic communities shoreline Pariaman. Study the theory used in this research, among others; (1) The study of semantics; (2) Naming; (3) a nickname; (4) The connotative meanings; (5) understanding of proper names; (6) the Minangkabau language. This study found 113 nickname used by Minangkabau ethnic communities in the Pariaman shoreline Pasisia. It can be concluded that in terms of form, found in two units lingual nickname: (1) the form of words and (2) are phrases, terms of reference unit forms lingual was formed on 8 reference / references a nickname in the form of (1) the physical condition , (2) behavior, (3) where / origin, (4) the name of the parents, (5) work, (6) status, (7) similarity, and (8) mental condition, based on the value of taste found three grades flavors, namely (1) the value of the negative sense, (2) the value of a positive sense, and (3) value neutral flavor.Â Keywords: proper names, Minangkabau ethnic